Reliability-based approach to the robustness of corroded reinforced concrete structures - Cavaco, Eduardo S.; Neves, Luís A.C.; Casas, Joan R. (Wiley Online, 2017)
Currently, decisions on the maintenance and repair of infrastructural assets, structures in particular, are mostly based on the results of inspections and the resulting condition index, neglecting system robustness and therefore not making optimal use of the limited funds available. This paper presents a definition and a measure of structural robustness in the context of deteriorating structures which are compatible with asset management systems for optimal maintenance and repair planning. The proposed index is used to define the robustness of existing reinforced concrete (RC) structures to rebar corrosion. Structural performance and the corresponding reliability index are assessed using combined advanced reliability and structural analysis techniques. Structural analysis explicitly includes deterioration mechanisms resulting from corrosion, such as reinforcement area reduction, concrete cracking, and bond deterioration. The first-order reliability method, combined with a response surface algorithm, is used to compute the reliability index for a wide range of different corrosion levels, resulting in a fragility curve. Finally, structural robustness is computed and discussed based on the results obtained. A robustness comparison of different structures can then be used to determine structural types more tolerant to corrosion and these results used for planning maintenance and repairs.